Geoinformatics and Extrapolation-based Applications for Estimation of Shortwave Radiation Potential as a Sustainable Energy Source: Emphasis on Smart Cities: Geoinformatics-based Estimation of Shortwave Radiation Potential as a Sustainable Energy Source - Sardar, Tariq; Raziq, Abdur; Rashid, Abdur (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2023)
Smart cities are objectively developed for a sustainable and better life quality for their inhabitants. The present study is focused on the determination of downward shortwave radiation potential-based sites to develop smart cities based on the suitability and useable aspect of these radiations as a sustainable energy source. The downward shortwave radiation is estimated through MTCLIM-XL extrapolation with further spatial-based potential through spatial analysis of Geographic Information System (GIS) as a Geoinformatics application an applicable tool of Geoinformatics majorly helps in integration and processing of related geo-data and related critical factors for final visualization towards smart and applicable decision making. Hence, these properties make Geoinformatics a viable approach in the applications of sustainable energy estimation for the development of smart and sustainable cities. Prospectively, Geoinformatics with the integration of related critical parameters can be a reliable approach for application in the determination of suitable locations for harvesting the radiation potential as a sustainable energy source.